Activation-induced deaminase is critical for the establishment of DNA methylation patterns prior to the germinal center reaction. Issue 9 (5th May 2021) - Català-Moll, Francesc; Ferreté-Bonastre, Anna G; Li, Tianlu; Weichenhan, Dieter; Lutsik, Pavlo; Ciudad, Laura; Álvarez-Prado, Ángel F; Rodríguez-Ubreva, Javier; Klemann, Christian; Speckmann, Carsten; Vilas-Zornoza, Amaya; Abolhassani, Hassan; et al.
Abstract: Activation-induced deaminase (AID) initiates antibody diversification in germinal center B cells by deaminating cytosines, leading to somatic hypermutation and class-switch recombination. Loss-of-function mutations in AID lead to hyper-IgM syndrome type 2 (HIGM2), a rare human primary antibody deficiency. AID-mediated deamination has been proposed as leading to active demethylation of 5-methycytosines in the DNA, although evidence both supports and casts doubt on such a role. In this study, using whole-genome bisulfite sequencing of HIGM2 B cells, we investigated direct AID involvement in active DNA demethylation. HIGM2 naïve and memory B cells both display widespread DNA methylation alterations, of which ∼25% are attributable to active DNA demethylation. For genes that undergo active demethylation that is impaired in HIGM2 individuals, our analysis indicates that AID is not directly involved. We demonstrate that the widespread alterations in the DNA methylation and expression profiles of HIGM2 naïve B cells result from premature overstimulation of the B-cell receptor prior to the germinal center reaction. Our data support a role for AID in B cell central tolerance in preventing the expansion of autoreactive cell clones, affecting the correct establishment of DNA methylation patterns.